Determinants of Maternal and Child Health Handbook Utilization in Surabaya, Indonesia - Irwanto, Irwanto; Ikhtiar, Ilham; Lutfiya, Indah; Purnomo, Windhu (Folia Medica Indonesiana, 2019)
Mothers and child health (MCH) are one of the main issues in family medicine. Related to this practice, Indonesian government issued mother and child health (MCH) handbook for monitoring child development due to various child developmental problems in Indonesia. However, there are reports of improper MCH handbook utilization. This study aimed to analyze factors related to the utilization of MCH handbook by mothers in Indonesia. Cross sectional observational study was conducted from March to May 2018. This study involved mothers with children aged 3 to 72 months old in Surabaya, East Java, Indonesia. Specific population of mothers who had children attending Early Childhood Education and Development (ECED) and Integrated Health Post (IHP) (Indonesia: Pos Pelayanan Terpadu-Posyandu) were included as inclusion criteria. Maternal characteristics, child health status, employment status, and utilization of MCH handbook were recorded through questionnaire. Association between variables then analyzed statistically using Spearman correlation test. As many as 288 participants were enrolled in this study. We found that mothers' participation of Posyandu was positively correlated with MCH handbook utilization (p<0.05). Meanwhile, mother's occupation (p>0.05), mothers' education (p>0.05), and maternal age (p>0.05) were found to be unrelated to the utilization of MCH handbook. Mothers' age, education, and employment were found to be uncorrelated with utilization of MCH handbook. Whereas, mothers' participation in Posyandu was a determinant factor correlated with utilization of MCH handbook.